ANALISIS SPASIAL DAN FAKTOR LINGKUNGAN YANG MEMPENGARUHI KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN LIMBOTO KABUPATEN GORONTALO - Ririn Pakaya; Lutfan Lazuardi; Hera Nirwati (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Background: Dengue Hemorrhagic Fever (DHF) is diseases caused by dengue virus. DHF transmitted by mosquito bites from Aedes genus Aedes, mainly Aedes aegypti or Aedes albopictus. DHF is emerging over the year and attacking all of age groups. It related to environmental condition and community behaviour. Incidence Rate (IR) of DHF from 1968 till now tend to showed improvement. Incidence rate of it showed extremely reduction from 2010 to 2011 and rising from 2012 to 2013 (41,25 per 100.000 person). DHF in Gorontalo has been endemic diseases every years and reported deaths of patient in this cases. Based on data of Districts Health Office Gorontalo, showed incidence of DHF has raised during last six years on 2010-2015. The extreme improvement DHF incidence on 2010 amounts 167 cases (3 person died) and the lowest reduction of DHF incidence on 2011 amounts 4 cases (1 person died). Objective: Identifying spatial distribution of DHF Incidence ana analyzing environment againts incidence of DHF in Limboto, Gorontalo.Method: Type of study was observational used cross sectional study design supported by Geographic information System (GIS) to collected spatial information.Result: Main result by poisson regression test showed association between physical environment variable such as precipitation (in same, previous, and previous two months), temperature (in same, previous, and previous two months), humidity (in same, previous, and previous two months), wind velocity (in same, previous, and previous two months). Variable of precipitation, humidity, and wind velocity in previous two months showed weak coefficient correlation and negative.Conclusion: Pattern of Dengue hemorrhagic fever (DHF) incidence following fluctuation of physical environment. Precipitation in previous two mounts, humidity, and wind velocity in same monts. The results show that the need for the District Health Office Gorontalo may considered physical environment factors on DHF’s prevention program.